Interaction between CO2 emissions trading and renewable energy subsidies under uncertainty: feed-in tariffs as a safety net against over-allocation. (14th September 2019) - Lecuyer, Oskar; Quirion, Philippe
ABSTRACT: We study the interactions between a CO2 emissions trading system (ETS) and renewable energy subsidies under uncertainty over electricity demand and energy costs. We develop an analytical model and a numerical model applied to the European Union electricity market in which renewable energy subsidies are justified only by CO2 abatement. We confirm that in this context, when uncertainty is small, renewable energy subsidies are not welfare-improving, but we show that when uncertainty is large enough, these subsidies increase expected welfare because they provide CO2 abatement even in the case of over-allocation, i.e. when the cap is higher than the emissions which would have occurred without the ETS. The source of uncertainty is important when comparing the various types of renewable energy subsidies. Under uncertainty over electricity demand, renewable energy costs or gas prices, a feed-in tariff brings higher expected welfare than a feed-in premium because it provides a higher subsidy when it is actually needed i.e. when the electricity price is low. Under uncertainty over coal prices, the opposite result holds true. Key policy insights Due to the possibility of over-allocation in an ETS, subsidies to renewable energies can increase expected welfare, even when climate change mitigation is the only benefit from renewables taken into account. In most cases studied, a feed-in tariff brings a higher expected welfare than a feed-in premium. The European Commission guidelines on State aid for energy, which incentivize member States to replace feed-in tariffs by feed-in premiums, should be reconsidered based on these results.